2015
DOI: 10.1186/s40064-015-1518-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel from coastal macroalgae (Chara vulgaris) and optimization of process parameters using Box-Behnken design

Abstract: Renewable biodiesels are needed as an alternative to petroleum-derived transport fuels, which contribute to global warming and are of limited availability. Algae biomass, are a potential source of renewable energy, and they can be converted into energy such as biofuels. This study introduces an integrated method for the production of biodiesel from Chara vulgaris algae collected from the coastal region of Bangladesh. The Box–Behnken design based on response surface methods (RSM) used as the statistical tool to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, in addition to the quantity of the algal sample, it could be concluded that the size of the algal particles also influenced in the final oil yield. [29,30]. Table 1: Amount of oil extracted using different solvent combination…”
Section: Effect Of Algal Amountmentioning
confidence: 99%
“…Therefore, in addition to the quantity of the algal sample, it could be concluded that the size of the algal particles also influenced in the final oil yield. [29,30]. Table 1: Amount of oil extracted using different solvent combination…”
Section: Effect Of Algal Amountmentioning
confidence: 99%
“…• Optimal conditions of biodiesel production for 12 g of dry algae are: 198 mL of chloroform, 0.75% NaCl, 65 C-yield 3.6 mL (0.3 mL/g dry weight) (Siddiqua, Mamun, & Enayetul Babar, 2015) • Padina tetrastromatica (B); Rameswaram, Mandapam Tamil Nadu, India…”
Section: Species Of Seaweedsmentioning
confidence: 99%
“…However, when more than one response must be optimized, it is necessary to use the so-called desirability functions [4]. RSM was often utilized to optimize different bioprocesses such as anaerobic digestion [5] and productions of bioethanol [6], lactic acid [7], triterpenoids [8], and biodiesel [9], among others. This methodology has also been successfully applied to xylose-to-xylitol bioconversion by the yeasts Candida tropicalis [10], Pachysolen tannophilus [11], Candida guilliermondii [12], and Debaryomyces hansenii [13].…”
Section: Introductionmentioning
confidence: 99%